KARAKTERISASI BIODIESEL PRODUK TRANSESTERIFIKASI MENGGUNAKAN VARIASI KECEPATAN SENTRIFUGASI PADA PROSES PEMISAHAN FAME - Sukhma Kusuma Dewi; Lilis Yuliati; Agung Sugeng Widodo (Jurnal Rekayasa Mesin, 2023)
The biodiesel production by transesterification method has five stages, namely: (1) the preparation process; (2) the transesterification process, (3) the separation process, (4) the washing process; and (5) the drying process. Separation occurs independently using a split funnel and gravity force, which takes approximately 120 minutes. The length of this separation process makes it less time efficient in the biodiesel production process. Therefore, a centrifuge separates FAME and glycerol while accelerating the process. This study aimed to determine the quantity and quality of biodiesel made from CPO and VCO using centrifugal speed and separation time variations. The rotation speed is varied between 2000 rpm and 4000 rpm, while the separation times are 5 minutes and 10 minutes. The result showed that the highest quantity of biodiesel from CPO and VCO was obtained using high centrifugation speeds of 4000 rpm and a 10-minute separation. The result showed biodiesel produced with this variation has good quality which met with SNI.